Dispersion‐Driven Conformational Isomerism in σ‐Bonded Dimers of Larger Acenes1. Issue 41 (23rd August 2013) - Ehrlich, Stephan; Bettinger, Holger F.; Grimme, Stefan
<x xml:space="preserve">Abstract</x> The σ‐bonded butterfly structure of the nonacene dimer shows unusual dispersion‐driven conformational isomerism that is due to strong intramolecular dispersion interactions between the wings of annulated aromatic rings. High‐level LPNO‐CEPA and DFT‐D3 ab initio calculations are in good mutual agreement, whereas dispersion‐devoid DFT and the MP2 method completely fail.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>